Self-Estimated Functional Inability because of Pain questionnaire for Brazilian workers with musculoskeletal pain: face and content validity - Cezar Augusto Brito Pinheiro; Cid André Fidelis-; Vinício dos Santos Barros; Josane Soares Pinto Melo; Daniela Bassi-Dibai; Almir Vieira Dibai-Filho (Universidade de São Paulo, 2021)
ABSTRACT Our study aimed to perform the face and content validity of Self-Estimated Functional Inability because of Pain (SEFIP) for workers, here called the SEFIP-work questionnaire. This is a questionnaire validity study. Our group previously translated and adapted the original version of the SEFIP, which was developed to investigate musculoskeletal pain and dysfunction to be applied to dancers (SEFIP-dance). However, due to the broad scope of the SEFIP-dance, we made changes and adaptations in the Brazilian Portuguese version of the SEFIP-dance to allow its use in workers. Therefore, face and content validity were performed for the development of the SEFIP-work based on opinions of committee of occupational disease and rehabilitation experts. After face and content validity, this SEFIP-work version was applied to 30 working individuals with musculoskeletal pain. The participants were native Brazilian Portuguese speakers aged 18 years and older. Thus, three changes were made to the questionnaire. All participants understood the SEFIP-work items and alternatives. The average total SEFIP-work score was 6.59 (SD=3.66), with the item "parte inferior das costas" (lower back) being the most marked (n=28; 93.33%), with an average score of 1.18 (SD=0.73). In conclusion, the Brazilian Portuguese version of SEFIP-work presents an acceptable level of understanding by workers in the investigation of musculoskeletal pain or discomfort.